Impact of Non-vitamin K Antagonist Oral Anticoagulant Withdrawal on Stroke Outcomes - Park, Joong Hyun; Han, Sang Won; Lee, Kyung-Yul; Choi, Hye-Yeon; Cheon, Kyeongyeol; Cho, Han-Jin; Jung, Yo Han; Park, Hyung Jong; Nam, Hyo Suk; Heo, Ji Hoe; Lee, Hye Sun; Saposnik, Gustavo; et al. (Frontiers in Neurology, 2018)
Introduction: Discontinuation of oral anticoagulants such as non-vitamin K antagonist oral anticoagulants (NOACs) may induce a hypercoagulable state, leading to severe stroke and poor outcomes. This study aimed to compare stroke outcomes between NOACs withdrawal and other prior medication status in patients with non-valvular atrial fibrillation (NVAF). Methods: Consecutive patients who had pre-existing NVAF and were admitted for an acute ischemic stroke or transient ischemic attack at five hospitals between January 2013 and December 2016 were included. Prior medication status was categorized into seven groups such as no antithrombotics, antiplatelet-only, warfarin with subtherapeutic intensity, warfarin with therapeutic intensity, NOAC, warfarin withdrawal, and NOAC withdrawal. We compared initial National Institute of Health Stroke Scale (NIHSS) scores between groups Results: Among 719 patients with NVAF, The median NIHSS score at admission was 5 (IQR 1-13). The NOAC withdrawal group had the highest median NIHSS scores at stroke onset (16, interquartile range, IQR [4-20]), followed by the warfarin withdrawal group (11, IQR [3-17]), the no antithrombotic group (5, IQR [2-16]), and the warfarin with subtherapeutic intensity group (5, IQR [2-13]). Multivariable analysis demonstrated that NOAC withdrawal was independently associated with higher NIHSS scores at stroke onset (B 4.645, 95% confidence interval 0.384–8.906, P=0.033). The median interval from drug withdrawal to ischemic stroke or TIA was 7 days (IQR 4-15) in the NOAC group. Conclusions: Stroke occurred after discontinuing oral anticoagulants, particularly NOAC, was independently associated with severe stroke at presentation.